Pengembangan E-LKPD Menggunakan Web Aplikasi Liveworksheet Berbasis Core (Connecting, Organizing, Reflecting, Dan Extending) Pada Materi Laju Reaksi - Siska Putri Afriyunni; Roza Linda; Erviyenni Erviyenni (FKIP University of Mataram, 2025)
This study aims to develop an E-LKPD based on the CORE (Connecting, Organizing, Reflecting, Extending) learning model by utilizing the Liveworksheets web application on the reaction rate material for grade XI of high school. The development was carried out using a 4-D model that includes the stages of defining, designing, and developing. The results of validation by material and media experts showed that the E-LKPD had met the validity criteria with consecutive scores in the aspects of content feasibility of 92.85%, CORE characteristics 87.51%, language 100%, presentation 87.5%, visual appearance and software use each 100%. The research sample used in this study were 10 grade XI students of SMAN 1 Pekanbaru and 10 grade XI students of SMAN 3 Pekanbaru. One-on-one and small group trials showed that students gave positive responses to the appearance, ease of use, and understanding of the E-LKPD content. In addition, teacher responses also showed that the E-LKPD was suitable for use in learning with a total percentage of 86.06%. Thus, the CORE-based E-LKPD using Liveworksheets on the demonstration rate material is declared valid and very feasible according to user assessments and can be used as an alternative digital-based interactive teaching material in the 21st century learning era.